Combinatorial exploration of the High Entropy Alloy System Co-Cr-Fe-Mn-Ni - Kauffmann, Alexander; Stüber, Michael; Leiste, Harald; Ulrich, Sven; Schlabach, Sabine; Szabó, Dorothée Vinga; Seils, Sascha; Gorr, Bronislava; Chen, Hans; Seifert, Hans-Jürgen; Heilmaier, Martin (Surface & coatings technology, 2017)
In high entropy alloys, the number of base alloying elements is increased to at least five and their individual concentrations are rather high in comparison to conventional metallic alloys. This strategy aims at maximization of the configurational part of entropy and stabilization of disordered, single-phase solid solutions with simple crystal structure. In the present contribution, a first attempt is presented for the exploration of the phase field of the face centered cubic solid solution in the vicinity of the well-known equimolar composition of CoCrFeMnNi (Cantor alloy) on the basis of combinatorial thin film deposition from sectioned, circular targets by magnetron sputtering. A variation of the chemical composition of the thin films from almost binary systems (for substrates placed on circular positions at the rim of the coated area) towards thin films with an almost equimolar composition (i.e. obtained for samples coated at the center region of the target) was achieved. Crystal structures of the binary thin films were studied and the according lattice parameters of body centered cubic, face centered cubic, hexagonally closed packed and complex cubic (α-Mn prototype) crystal structures are in good accordance with expectations for solid solutions from literature data. The microstructure of the face centered solid solution thin films deposited at the center region of the target was investigated in detail by transmission electron microscopy and atom probe tomography. An ultra-fine grained, columnar microstructure was found exhibiting disorder down to atomic length scale. Thus, a suitable platform for future investigations of the entire face centered cubic phase field is provided and the strength of the combinatorial thin film approach for the investigation of complex microstructure development in high entropy alloy systems is revealed. •Combinatorial deposition of Co-Cr-Fe-Mn-Ni thin films from sectioned targets•Crystal structures of pseudo-binary solid solutions were identified.•Lattice parameters are in good agreement with expectations from literature data.•FCC high entropy alloy with ultra-fine grained microstructure in the center region•Disorder is revealed down to atomic length scale with absence of phase separation.